2020
DOI: 10.1101/2020.11.10.376350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mixed-stock analysis in the age of genomics: Rapture genotyping enables evaluation of stock-specific exploitation in a freshwater fish population with weak genetic structure

Abstract: Mixed-stock analyses using genetic markers have informed fisheries management in cases where strong genetic differentiation occurs among local spawning populations, yet many fisheries are supported by multiple spawning stocks that are weakly differentiated. Freshwater fisheries exemplify this problem, with many harvested populations supported by multiple stocks of young evolutionary age that are isolated across small spatial scales. As a result, attempts to conduct genetic mixed-stock analyses of inland fisher… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 96 publications
(152 reference statements)
1
0
0
Order By: Relevance
“…In contrast, gizzard shad and emerald shiner, which had low levels of structure in our study, are both broadcast spawners, allowing their eggs to be carried freely by the currents, facilitating gene flow. Genetic studies on similar fish species have generally corroborated the patterns we observed, with nest-spawning species such as smallmouth bass (Micropterus dolomieu) exhibiting high levels of genetic structure in open systems compared to broadcast-spawning species such as walleye (Sander vitreus) (Euclide et al, 2020(Euclide et al, , 2021Ruzich et al, 2019).…”
Section: Neutral Population Structure Reflects the Difference In Life...supporting
confidence: 76%
“…In contrast, gizzard shad and emerald shiner, which had low levels of structure in our study, are both broadcast spawners, allowing their eggs to be carried freely by the currents, facilitating gene flow. Genetic studies on similar fish species have generally corroborated the patterns we observed, with nest-spawning species such as smallmouth bass (Micropterus dolomieu) exhibiting high levels of genetic structure in open systems compared to broadcast-spawning species such as walleye (Sander vitreus) (Euclide et al, 2020(Euclide et al, , 2021Ruzich et al, 2019).…”
Section: Neutral Population Structure Reflects the Difference In Life...supporting
confidence: 76%